RELEVANSI NILAI DIVIDEND YIELD DAN RASIO P/E DENGAN PERTUMBUHAN PERUSAHAAN - Saputro, Julianto Agung (Journal of Indonesian Economy and Business, 2002)
Analysts use valuation model in determining and evaluating share prices. Survey evidence suggests that the dominant valuation model is the price-earnings (P/E) ratio, but that other approaches such as the dividend yield are also important. This study develops and tests a market valuation models whose main prediction is that equity value is a function of earnings, dividends and book value. This study demonstrates that growth firms relevant use P/E ratio approach, and that not growth firms more relevant use dividend yield ratio approach than P/E ratio.Keywords: P/E ratio, dividend yield, market valution model, growth firm